Lola regulates glutamate receptor expression at the Drosophila neuromuscular junction. - Fukui, A.; Inaki, M.; Tonoe, G.; Hamatani, H.; Homma, M.; Morimoto, T.; Aburatani, H.; Nose, A. (Biology open, 2012)
Communication between pre- and post-synaptic cells is a key process in the development and modulation of synapses. Reciprocal induction between pre- and postsynaptic cells involves regulation of gene transcription, yet the underlying genetic program remains largely unknown. To investigate how innervation-dependent gene expression in postsynaptic cells supports synaptic differentiation, we performed comparative microarray analysis of Drosophila muscles before and after innervation, and of prospero mutants, which show a delay in motor axon outgrowth. We identified 84 candidate genes that are potentially up- or downregulated in response to innervation. By systematic functional analysis, we found that one of the downregulated genes, longitudinals lacking (lola), which encodes a BTB-Zn-finger transcription factor, is required for proper expression of glutamate receptors. When the function of lola was knocked down in muscles by RNAi, the abundance of glutamate receptors (GluRs), GluRIIA, GluRIIB and GluRIII, as well as that of p-21 activated kinase (PAK), was greatly reduced at the neuromuscular junctions (NMJs). Recordings of the synaptic response revealed a decrease in postsynaptic quantal size, consistent with the reduction in GluR levels. Lola appears to regulate the expression of GluRs and PAK at the level of transcription, because the amount of mRNAs encoding these molecules was also reduced in the mutants. The transcriptional level of lola, in turn, is downregulated by increased neural activity. We propose that Lola coordinates expression of multiple postsynaptic components by transcriptional regulation.